The Child Affective Facial Expression (CAFE) set: validity and reliability from untrained adults - LoBue, Vanessa; Thrasher, Cat (Frontiers in Psychology, 2015)
Emotional development is one of the largest and most productive areas of psychological research. For decades, researchers have been fascinated by how humans respond to, detect, and interpret emotional facial expressions. Much of the research in this area has relied on controlled stimulus sets of adults posing various facial expressions. Here we introduce a new stimulus set of emotional facial expressions into the domain of research on emotional development—The Child Affective Facial Expression set (CAFE). The CAFE set features photographs of a racially and ethnically diverse group of 2- to 8-year-old children posing for 6 emotional facial expressions—angry, fearful, sad, happy, surprised, and disgusted—and a neutral face. In the current work, we describe the set and report validity and reliability data on the set from 100 untrained adult participants.